The Roles of Supervisory Support and Involvement in Influencing Scientists' Job Satisfaction to Ensure the Achievement of SDGs in Academic Organizations. (July 2021) - Ghasemy, Majid; Rosa-Díaz, Isabel Maria; Gaskin, James Eric
Job satisfaction is the focus of this study, given its strategic importance, both to generate differentiation and competitive advantages, and to promote better and more sustainable results in organizations. Guided by the Affective Events Theory (AET), the interest is in analyzing the direct and indirect effects of supervisory support and involvement on job satisfaction and highlighting the implications of the academics' emotions for sustainability-related policies and practices in academic environments. The context selected is the higher education (HE) sector in Malaysia for science disciplines, due to its socio-economic relevance and its direct link to the Fourth Industrial Revolution (IR4), as well as to the Sustainable Development Goals (SDGs). A sample of 579 scientists were selected randomly and the analysis was carried out based on partial least squares structural equation modeling (PLS-SEM) methodology. Our results supported the hypotheses postulated in the study and especially highlighted the effects of supervisory support and positive affect on job satisfaction, as well as the effect of interpersonal conflict on negative affect. In terms of implications, policy makers at ministry level are advised to consider introducing directives which promote a climate of emotional safety and trust in academic institutions, to achieve the SDGs more effectively and efficiently. At the university level, and given the relevance of the observed effects, academic leaders are recommended to contemplate improving university environments in some way that reduces levels of negative work events (interpersonal conflict in our case). This is crucial as the negative work events can trigger negative emotions, which in turn cause scientists' job dissatisfaction.